Ansiolytic effect of essential oils: a review on pre-clinical and clinical studies (Research, Society and Development, 2020)
Anxiety participates in the body's natural defense, however, it can be pathological, when symptoms start to interfere in the individual's routine, causing loss of quality of life. Essential oils (EOs) are secondary metabolites with numerous pharmacological and biological activities, where we can highlight anxiolytic activity. Thus, the objective was to carry out a systematic review of the last 9 years in the large area of ​​pharmacology and toxicology, and to verify which EOs have anxiolytic activity, which tests were performed and the possible mechanisms involved. A bibliographic review with a qualitative and quantitative nature was carried out, using the Scopus database, where original studies were published, published between January 2010 and August 10, 2019, of the pre-clinical and clinical trial type that present results referring to anxiolytic activity of EOs, excluding those studies that did not understand the area of ​​pharmacology and / or toxicology. At the end of this analysis, of the 71 papers found, 18 were selected to compose this review. This review made it possible to visualize the panorama of preclinical and clinical studies for assessing anxiety with the use of OEs in the last 9 years, pointing out that in addition to the EO of Lavandula angustifolia, other EOs can also be promising, such as the EOs obtained from species of the genus Citrus. However, there is a scarcity of clinical studies to prove the efficacy and safety of the use of these EOs in the treatment of anxiety, which allows the opening of research in this area for the development and launch of new natural anxiolytics.